Observation of lambda 0b → psi(2S)pK- and lambda 0b → J/psiπ + π -pK- decays and a measurement of the lambda 0b baryon mass - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; et al. (Journal of high energy physics, 2016)
The decays Λb0 → ψ(2S)pK− and Λb0 → J/ψπ+π−pK− are observed in a data sample corresponding to an integrated luminosity of 3 fb−1, collected in proton-proton collisions at 7 and 8 TeV centre-of-mass energies by the LHCb detector. The ψ(2S) mesons are reconstructed through the decay modes ψ(2S) → μ+μ− and ψ(2S) → J/ψπ+π−.
*The LHCb collaboration: R. Aaij, P. D'Argent, S. Bachmann, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, S. Esen, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kecke, M. Kolpin, K. Kreplin, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Stahl, U. Uwer, M. Vesterinen, A. Zhelezov [und sehr viele weitere Personen]
Im Titel sind "Lambda" und "psi" als griechische Buchstaben dargestellt
Im Titel sind die Zahl 0 und die Zeichen + und - hochgestellt
Im Titel ist der Buchstabe b tiefgestellt
Gesehen am 17.07.2020